Direct Observation of Dirac Cone in Multilayer Silicene Intercalation Compound CaSi2. (15th December 2014) - Noguchi, Eiichi; Sugawara, Katsuaki; Yaokawa, Ritsuko; Hitosugi, Taro; Nakano, Hideyuki; Takahashi, Takashi
<x xml:space="preserve">Abstract</x> Calcium‐intercalated multilayer silicene CaSi 2 exhibits a massless Dirac‐cone π‐electron‐band dispersion like graphene, while the Dirac point is about 2 eV away from the Fermi level due to diiimide‐based charge transfer from the Ca atoms to the silicene layers. This indicates that the graphene‐like electronic structure with a massless Dirac cone is stably formed in the metal‐intercalated multilayer silicene. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>